Estudo teórico e aplicações dos absorvedores dinâmicos de vibrações - Mollica, Guilherme Henrique Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Undesired vibrations can lead to problems as structural damage and even affect human health. There are a great number of ways of controlling these vibrations. Dynamic vibration absorbers are devices that have a series of advantages when compared with other methods of control. They are fixed at the main structure, in which it is desired to neutralize excessive vibrations. DVAs devices can be classified into passive, adaptive and active ones. Passive DVAs are the simplest, cheapest and most practical type. Its utilization will take place when the frequency of excitation is not variable, since its frequency band of operation is relatively narrow. To avoid this problem new types of DVAs were introduced, known as adaptive DVA and active DVA. Physical parameters of adaptive DVAs, like stiffness, damping and mass can be varied so that the DVA can be tuned to a desired frequency. Active DVAs consist of an actuator parallel to a resilient element. This actuator is controlled by a control law. The applicability of each type of DVA varies according to external characteristics, like the frequency of excitation, the capacity of the system to provide energy to the DVA, the cost of implementation and the efficiency required. Passive DVAs are very practical and have a low-cost implementation, however, the range of frequency for which they are effective is very small. On the other hand, active DVAs require a large amount of energy to operate, although its operational range of frequency is very broad. Therefore, depending on the system where the control of the undesired vibrations is needed, a specific type of DVA will be recommended

Vibrações indesejadas podem levar a problemas como danos em estruturas e até mesmo afetar a saúde humana. Há diversos modos de controle dessas vibrações. Absorvedores dinâmico de vibrações são dispositivos que apresentam uma série de vantagens em relação a outros modos de controle. Eles são fixados na estrutura principal, na qual se deseja neutralizar uma vibração excessiva. ADVs podem ser classificados em passivos, adaptativos e ativos. Os ADVs passivos são o tipo mais simples, barato e prático. Sua utilização ocorrerá quando a frequência de excitação não for variável, já que sua banda de frequência de operação é relativamente estreita. Em ordem de evitar este problema foram introduzidos novos tipos de ADVs, conhecidos como ADVs adaptativos e ativos. Os parâmetros físicos como rigidez, amortecimento e massa dos ADVs adaptativos podem ser variados para que o ADV seja sintonizado na frequência desejada. ADVs ativos constituem de um atuador em paralelo com um elemento resiliente. Esse atuador é controlado por uma lei de controle e exerce uma força na massa principal a fim de atenuar vibrações excessivas. A aplicabilidade de cada tipo de ADV varia de acordo com características externas, como a frequência de excitação, a capacidade do sistema de fornecer energia para o ADV, o custo de implementação e a eficiência desejada. ADVs passivos são muito práticos e apresentam um baixo custo de implementação, contudo só trabalham em uma faixa estreita de frequências. Já os ADVs ativos requerem uma grande quantidade de energia para seu funcionamento, contudo sua gama de frequência de operação é bem mais ampla. Portanto, dependendo das características do sistema que se deseja controlar as vibrações indesejadas, um tipo específico de ADV será recomendado
Theoretical study and applications of dynamic vibration absorbers
Keywords: Vibração; Absorvedores; Dinâmica estrutural; Vibration